2008
DOI: 10.1002/path.2328
|View full text |Cite
|
Sign up to set email alerts
|

Functional and phenotypic characteristics of testicular macrophages in experimental autoimmune orchitis

Abstract: Testicular inflammation with compromised fertility can occur despite the fact that the testis is considered an immunoprivileged organ. Testicular macrophages have been described as cells with an immunosuppressor profile, thus contributing to the immunoprivilege of the testis. Experimental autoimmune orchitis (EAO) is a model of organ-specific autoimmunity and testicular inflammation. EAO is characterized by an interstitial inflammatory mononuclear cell infiltration, damage of the seminiferous tubules and germ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 32 publications
3
88
0
Order By: Relevance
“…In immunohistochemical studies on testicular cytokines, it was revealed that testicular interstitial cells were positive for IFN-γ and TNF-α antibodies in EAO [7,19]. Enzyme-linked immunosorbent assays of testicular macrophages isolated from EAO-affected testes also demonstrated that these two cytokines were significantly secreted into the culture supernatant [8,9]. However, a real-time RT-PCR study of isolated dendritic cells obtained from TH+CFA+BP-EAOaffected testes did not show a significant change in TNF-α mRNA expression [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In immunohistochemical studies on testicular cytokines, it was revealed that testicular interstitial cells were positive for IFN-γ and TNF-α antibodies in EAO [7,19]. Enzyme-linked immunosorbent assays of testicular macrophages isolated from EAO-affected testes also demonstrated that these two cytokines were significantly secreted into the culture supernatant [8,9]. However, a real-time RT-PCR study of isolated dendritic cells obtained from TH+CFA+BP-EAOaffected testes did not show a significant change in TNF-α mRNA expression [20].…”
Section: Discussionmentioning
confidence: 96%
“…It has also been reported that the disease can be suppressed in vivo by the administration of anti-TNF-α antibodies but not anti-IFN-γ antibodies [6]. In rat EAO induced by immunization with TH+CFA+BP, it was shown that isolated testicular macrophages secreted both IFN-γ and TNF-α [7][8][9]. However, the intratesticular changes in IFN-γ and TNF-α mRNA expression at the organ level have not yet been investigated in any EAO model.…”
mentioning
confidence: 99%
“…By contrast, circulating macrophages significantly infiltrate the testis in orchitis and are detrimental to spermatogenesis. 40,41 Clinical observation revealed high macrophage numbers in the testis of patients with aspermatogenesis and infertility indicating a negative correlation between circulating macrophages and spermatogenesis. 42 Dendritic cells (DCs) exist in the testicular interstitial spaces and represent a minor population of the interstitial cells in the normal testis, reaching one-tenth of the numbers of macrophages.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…Induced by immunization with testicular homogenate in adjuvant, EAO is characterized by the production of auto-antibodies against testicular Ags, elevated levels of proinflammatory cytokines (e.g., TNFa, IL-6) or chemokines (e.g., MCP-1), followed by the infiltration of leukocytes (mainly macrophages, dendritic cells, T lymphocytes) (12)(13)(14). An increase in the number of regulatory CD4 + CD25 + Foxp3 + T cells is also observed (15).…”
mentioning
confidence: 99%